Non-invasive biomarkers to diagnose and monitor eosinophilic esophagitis: a systematic review - Noble, Sophia-Louise; Tyrrell, Richard; Mules, Thomas C.; Inns, Stephen (Frontiers in Medicine, 2025)
Background and aimsCurrent assessments for diagnosing and monitoring eosinophilic esophagitis (EoE) are invasive, time-intensive and costly. The development of non-invasive biomarkers that are sensitive and specific for EoE is paramount. We aimed to provide a comprehensive update on the latest biomarker discovery research in EoE and discuss the current state of the field.MethodsPubMed, Web of Science, Medline and Embase were searched for studies on non-invasive biomarkers for EoE. Extracted studies were analyzed for risk of bias and relevant data was extracted, including study design, participants, information on controls, biomarker detection method, biomarkers studied, and biomarkers for which statistical significance was found.ResultsOf the 239 studies identified, 37 articles met the inclusion criteria and were included in the systematic review. Across these studies, over 80 biomarkers were evaluated as potential non-invasive tools for diagnosing and monitoring EoE. While the most commonly investigated biomarker was peripheral eosinophil count (PEC), overall PEC demonstrated limited reliability. Other emerging biomarkers, including eosinophil-derived proteins (e.g., EDN, MBP-1) and cytokines (e.g., eotaxin-3), showed promise, although findings were inconsistent between studies. Esophageal-specific sampling methods, such as the Cytosponge, esophageal string test (EST), and esophageal brushings, demonstrated strong correlations with histologic eosinophil counts and disease activity, particularly through the measurement of eosinophil-associated proteins.ConclusionEsophageal-specific sampling methods show significant promise for accurately diagnosing and monitoring EoE, particularly through eosinophil-derived biomarkers, such as eosinophil-derived neurotoxin (EDN). Furthermore, these methods were better tolerated and more cost-effective compared to endoscopy and biopsy.